POLA SEBARAN HORIZONTAL DAN KERAPATAN PLANKTON Di PERAIRAN BAWEAN - Djumanto Djumanto; Tumpak Sidabutar; Hanny Pontororing; Reinhard Leipary (Universitas Gadjah Mada, 2009)
The objectives of this research were to find out the horizontal distribution patterns, the density and species dominancy of plankton in Bawean waters, Gresik regency. Sampling was done using RV Baruna Jaya VIII on 29-30 April 2009. There were 12 stations for sampling, which arranged latitude 3 stations to the north and longitude 4 stations to the east with the distance of 8 and 12 miles, respectively. Water samples were collected using Kitahara net for phytoplankton and Norpac net for zooplankton by filtering from bottom to surface. The density of plankton for each station was measured base on their biovolume bases, namely settlement for phytoplankton whereas water replacement for zooplankton. Genus of plankton was identified for each station.The results showed that the highest density of phytoplankton was found in the northern part and was decreased towards the south, while the highest zooplankton was found in the middle area. The density of phytoplankton was distributed homogeneously, while zooplankton was distributed randomly. The density of biomass phytoplankton ranged from 0.294-3.985 ml/rn3 and an average wasl.598 ml/m3. The density of biomass zooplankton ranged from 0.05-0.24 ml/m3, and an average was 0.122 ml/m3. The ratio of biovolume between phytoplankton and zooplankton ranged from 3:1-31:1 with an average was 13:1. The individual density of phytoplankton ranged from 15,843 - 1,755,694 individual/m3, while zooplankton was between 861-29,362 individual/m3. In the phytoplankton was found as much as 34 genus, and there were 5 genus which their populations were abundantly, namely Caetoceros, Skeletonema, Rizosolenia, Pleurosigma and bacteriostratum with percentage of 25,34%, 24,45%, 13,84%, 10,68% and 8,10%, respectively. The biology index of phytoplankton, namely diversity (H) ranged from 1.11-2.22, uniformities (E) ranged from 0.50- 1.00, and dominancy (D) ranged from 0.16 - 0.50. in the zooplankton was found 65 genus, and there were 5 genus of their populations was abundantly, that was Ceratium, Calanus, Cetocerelia, Agalma and Fritillaria with percentage 22.26%, 17.10%, 6.96%, 6.92% and 5.21%, respectively. The diversity index of zooplankton ranged from 1.83 - 2.56, uniformities ranged from 0.791.00, and dominancy ranged from 0.12-0.23. The population forming of phytoplankton and zooplankton were very assorted and dynamic.